Antimicrobial susceptibility of Neisseria gonorrhoeae in Zaire: high level plasmid-mediated tetracycline resistance in central Africa. Issue 2 (April 1992) - Van Dyck, E; Rossau, R; Duhamel, M; Behets, F; Laga, M; Nzila, M; Bygdeman, S; Van Heuverswijn, H; Piot, P
Abstract : OBJECTIVE–To determine the in vitro antimicrobial susceptibility of gonococcal strains isolated in 1988 among female prostitutes in Kinshasa, Zaire and to characterise strains with high level tetracycline resistance. METHODS–Minimal inhibitory concentrations of 8 antimicrobials were measured by agar dilution technique. Plasmid-profiles and serovars were determined. RESULTS–Two hundred and thirteen strains of Neisseria gonorrhoeae were tested of which 59% were beta-lactamase producers and an additional 21% showed intermediate or chromosomal resistance to penicillin (MIC = 0.5-8 mg/l). Eleven percent of the strains were resistant to the combination sulfamethoxazole-trimethoprim (MIC greater than 8 mg/l) and 57% of the isolates showed decreased susceptibility to thiamphenicol (MIC = 1-4 mg/l). All strains were sensitive to spectinomycin, norfloxacin and ceftriaxone and moderately sensitive to kanamycin. Chromosomal resistance to tetracycline was observed in 45% of strains (MIC = 2-8 mg/l). Ten percent were highly resistant to tetracycline (TRNG, MIC = 16-128 mg/l) and were shown to carry a plasmid borne Tet M determinant; such strains were not found in Kinshasa in 1985. TRNG belonged to 4 different serovars, which were also the dominant serovars in non-TRNG. CONCLUSION–These findings illustrate the high frequency of multiresistant gonococci in Zaire and suggest that high level tetracycline resistant strains of N. gonorrhoeae have become endemic in Central Africa.